Influência dos diferentes ácidos graxos da dieta sobre um modelo animal de mania induzido por anfetamina em ratos - Trevizol, Fabíola (2010)
Fatty acids (FA) are constituent important of the neuronal phospholipids membranes and they carry out important functions in the development and function of the brain During the last decades changes were observed in the feeding habits of western countries, with an increase of the trans FA and omega-6 (n-6) and detriment of omega-3 fatty acids (n-3) consumption, contributing to increase the oxidative stress (OS) generation and development of neuropsychiatric disorders. The influence of FA supplementation containing n-6 (soybean oil-SO), trans (hydrogenated vegetable fat-HVF) and n-3 (fish oil-FO) on behavioral parameters and OS were studied in an animal model of mania. Rats were orally treated for 8 weeks with suspensions of SO, HVF and FO in place of drinking water, and treated with seven daily administrations of amphetamine (AMPH-mg/kg, ip) or vehicle, in the last week of oral treatment. Locomotor activity, vitamin C (VIT C) levels, protein oxidation and mitochondrial slices in striatum and cortex were evaluated. HVF supplemented rats showed an increase in the locomotor activity, higher levels of carbonyl protein in the cortex, and lower mitochondrial viability in the striatum and cortex, showing harmful effects per se. AMPH treatment increased the locomotor activity of all groups, but this effect showed greater intensity in the rats orally treated with HVF (456%). Similarly, AMPH increased the carbonyl protein levels in striatum (39.5%) and cortex (78%) of the animals orally treated with HVF, while SO and FO prevented it in the cortex. AMPH treatment decreased the mitochondrial viability in cortex and striatum of supplemented rats with all the FA; however the HVF group showed greater damage (46 and 44% of viability in the striatum and cortex, respectively). AMPH reduced the VIT C plasma levels of the HVF and SO groups (22.5 and 22.4% respectively), and this antioxidant parameter has not been changed in the FO treated rats. Here, we suggest that the trans FA contained in the HVF may increase the oxidative damages per se, leaving the rats more vulnerable to AMPH damage. FA n-3 contained in the FO showed subtle protecting effects, which were observed by preservation of the VIT C levels and lower levels of carbonyl protein in the cortex. Further studies should be conducted to evaluate the influence of the trans fatty acids consumption on neuronal activity, and consequently on the susceptibility to psychiatric disorders development among them the bipolar disorder.